Leaf extracts from Dendropanax morbifera Léveille mitigate mercury-induced reduction of spatial memory, as well as cell proliferation, and neuroblast differentiation in rat dentate gyrus - Woosuk Kim; Dae Young Yoo; Hyo Young Jung; Jong Whi Kim; Kyu Ri Hahn; Hyun Jung Kwon; Miyoung Yoo; Sanghee Lee; Sung Min Nam; Yeo Sung Yoon; Dae Won Kim; In Koo Hwang (BMC Complementary and Alternative Medicine, 2019)
Abstract Background The brain is susceptible to methylmercury toxicity, which causes irreversible damage to neurons and glia and the leaf extract Dendropanax morbifera Léveille (DML) has various biological functions in the nervous system. In this study, we examined the effects of DML on mercury-induced proliferating cells and differentiated neuroblasts. Methods Dimethylmercury (5 μg/kg) and galantamine (5 mg/kg) was administered intraperitoneally and/or DML (100 mg/kg) was orally to 7-week-old rats every day for 36 days. One hour after the treatment, novel object recognition test was examined. In addition, spatial probe tests were conducted on the 6th day after 5 days of continuous training in the Morris swim maze. Thereafter, the rats were euthanized for immunohistochemical staining analysis with Ki67 and doublecortin and measurement for acetylcholinesterase (AChE) activity. Results Dimethylmercury-treated rats showed reduced discrimination index in novel object recognition test and took longer to find the platform than did control group. Compared with dimethylmercury treatment alone, supplementation with DML or galatamine significantly ameliorated the reduction of discrimination index and reduced the time spent to find the platform. In addition, the number of platform crossings was lower in the dimethylmercury-treated group than in controls, while the administration of DML or galantamine significantly increased the number of crossings than did dimethylmercury treatment alone. Proliferating cells and differentiated neuroblasts, assessed by Ki67 and doublecortin immunohistochemical staining was significantly decreased in the dimethylmercury treated group versus controls. Supplementation with DML or galantamine significantly increased the number of proliferating cells and differentiated neuroblasts in the dentate gyrus. In addition, treatment with dimethylmercury significantly increased AChE activity in hippocampal homogenates, while treatment with dimethylmercury+DML or dimethylmercury+galantamine significantly ameliorated this increase. Conclusions These results suggest that DML may be a functional food that improves dimethylmercury-induced memory impairment and ameliorates dimethylmercury-induced reduction in proliferating cells and differentiated neuroblasts, and demonstrates corresponding activation of AChE activity in the dentate gyrus.